Kajian Sifat Fisika Tanah Ultisol Pra dan Pasca Penanaman Padi Sawah - Muhammad Holqi Rahmadani; Muhammad Syarbini; Akhmad Rizalli Saidy (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2024)
This research is motivated by the conversion of many rice fields in Indonesia for various purposes, such as residential areas, offices, industries, tourism, transportation, and other uses. The environmental change focused on in this study is the conversion of Ultisol land into paddy fields. The aim of the research is to determine the differences in soil physical properties, including grain density, bulk density, soil porosity, permeability, and soil aggregate stability in Ultisol that have been subjected to inundation. The study follows a Completely Randomized Design (CRD) with a single factor. The factor tested is the origin of Ultisol soil taken from five different districts in South Kalimantan. Soil samples represent the distinct districts, and each district is replicated five times. Paired t-test is employed to observe the differences in the physical properties of inundated and non-inundated Ultisol. Incubation and physics analysis are carried out at the Greenhouse of the Soil Department and the Physics, Chemistry, and Biology Laboratory of the Soil Department, Faculty of Agriculture, Lambung Mangkurat University. The results indicate that inundation in Ultisol soil does not significantly affect soil density and soil porosity. Inundation, however, significantly differs in soil bulk density, permeability, and soil aggregate stability. Changes in soil physical properties are not correlated with plant dry weight.